2014
DOI: 10.1021/ic502380q
|View full text |Cite
|
Sign up to set email alerts
|

Proline Functionalization of the Mesoporous Metal−Organic Framework DUT-32

Abstract: The linker functionalization strategy was applied to incorporate proline moieties into a metal−organic framework (MOF). When 4,4′-biphenyldicarboxylic acid was replaced with a Boc-protected proline-functionalized linker (H 2 L) in the synthesis of DUT-32 (DUT = Dresden University of Technology), a highly porous enantiomerically pure MOF (DUT-32-NHProBoc) was obtained, as could be confirmed by enantioselective high-performance liquid chromatography (HPLC) measurements and solid-state NMR experiments. Isotope la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 20 publications
0
66
0
Order By: Relevance
“…Thisw as not expected due to the mild synthesis conditions used and racemisation of l-Pro upon PSMw as previously reported only for the post-synthetic thermal deprotection of DUT-32-NHPro. [60] The other resonances for l-Pro are also split with the C2 signal at 62.0 and 60.5 ppm, C5 at 50.2 and 48.1 ppm, and C3 and C4 at 37.9, 33.7, 31.4, 29.6 and 28.7 ppm.…”
Section: Resultsmentioning
confidence: 98%
“…Thisw as not expected due to the mild synthesis conditions used and racemisation of l-Pro upon PSMw as previously reported only for the post-synthetic thermal deprotection of DUT-32-NHPro. [60] The other resonances for l-Pro are also split with the C2 signal at 62.0 and 60.5 ppm, C5 at 50.2 and 48.1 ppm, and C3 and C4 at 37.9, 33.7, 31.4, 29.6 and 28.7 ppm.…”
Section: Resultsmentioning
confidence: 98%
“…This one‐fell‐swoop assembly of primitive ligands and their fragments not only introduces functional groups in originally microporous MOFs, but also functionalized cavities, bringing considerable improvement to the mass transport of the resulting hierarchical micro‐ and mesoporous MOFs. Kutzscher et al reported the proline functionalization of the linker of mesoporous DUT‐32 (DUT refers to Dresden University of Technology), and the product exhibits the high liquid‐phase adsorption capacity with ethyl cinnamate . Liu et al proposed strain‐promoted “click” chemistry, which can be used to introduce different functional groups into the mesopores of MOFs.…”
Section: Fabrication Strategies To Mesoporositymentioning
confidence: 99%
“…Among the applications, immobilization of homogeneous catalysts, especially chiral catalysts, on cavity surfaces of the solid porous materials is of great importance. In this field, the latest developments involved enantioselective catalysis based on metal-organic frameworks (MOFs) [1][2][3][4][5][6][7][8][9][10][11][12][13][14], covalent organic frameworks (COFs) [15][16][17][18][19][20][21][22][23][24] and porous organic polymers (POPs) [25][26][27][28][29][30][31][32]. Many advantages of MOFs, COFs and POPs for heterogeneous enantioselective catalysis have been elaborated by scientists.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, owing to the appropriate size as well as the easy preparation, the proline-type organocatalysts are one of the best candidates to investigate if a new solid material could be used as the platform for enantioselective catalysis. On the other hand, the Aldol reaction is an important reaction which is frequentlyused to investigate the catalytic activity of the catalyst supported by porous materials such as MOFs, COFs and POPs [1][2][3][4][5][6][7][8][9]23,24,32]. Thus in this paper we make an attempt to introduce the chiral catalytically active L-prolinamide unit into the PAF-1 material by stepwise post-synthetic modifications and investigate the catalytic performance of the obtained material for catalyzing the Aldol reaction.…”
Section: Introductionmentioning
confidence: 99%